2018
DOI: 10.1016/j.erss.2018.03.028
|View full text |Cite
|
Sign up to set email alerts
|

A political economy of niche-building: Neoliberal-developmental encounters in photovoltaic electrification in Kenya

Abstract: International agreements on energy access and climate change, formulated according to neoliberal orthodoxy, will drive significant finance to developing countries for clean technology investments. But critics call for more active state intervention-a developmental approach-arguing that free markets alone will not deliver what is required. This creates the potential for confrontation between contradictory ideologies in national policymaking and implementation: neoliberalism in global agreements versus developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…That said, in the case of political economy theory, examples do exist of scholars who have successfully acknowledged the value of innovation capabilities (a core tenet of innovation systems thinking) in their analysis (see [60]). And, as demonstrated in a recent special issue (see [30]), it seems to be increasingly common in the contemporary, critical social science literature on energy access to find examples of scholars using social practice, innovation systems, or political economy theory (the latter also including the work by Newell and Phillips [56] and Byrne et al [16] mentioned in Section 5.3 above) to drill down in more detail on specific aspects of the multi-level perspective [38] that has been so influential in socio-technical transitions thinking.…”
Section: Overarching Conceptual Framework Pragmatic Interdisciplinmentioning
confidence: 99%
See 4 more Smart Citations
“…That said, in the case of political economy theory, examples do exist of scholars who have successfully acknowledged the value of innovation capabilities (a core tenet of innovation systems thinking) in their analysis (see [60]). And, as demonstrated in a recent special issue (see [30]), it seems to be increasingly common in the contemporary, critical social science literature on energy access to find examples of scholars using social practice, innovation systems, or political economy theory (the latter also including the work by Newell and Phillips [56] and Byrne et al [16] mentioned in Section 5.3 above) to drill down in more detail on specific aspects of the multi-level perspective [38] that has been so influential in socio-technical transitions thinking.…”
Section: Overarching Conceptual Framework Pragmatic Interdisciplinmentioning
confidence: 99%
“…The latter casts analytical attention on the ways technology and innovation co-evolve with social practices and broader social institutions, creating dominant socio-technical regimes and path dependency that new niches of sustainable technology struggle to compete with and influence in new, sustainable directions. Importantly, as several authors have now shown in relation to energy access (e.g., [8,16,[39][40][41][42]), these socio-technical regimes can look different in remote areas of low-income countries to those studied in the Global North; the latter being the empirical context within which the majority of the socio-technical transitions literature has emerged to date (as analysed, for example, in a recent special issue, see [43,44]). Nevertheless, as demonstrated by the aforementioned recent contributions, these low-income contexts are still subject to similar dynamics, where everyday practices and powerful economic and political interests align with dominant socio-technical regimes (e.g., in the supply of kerosene for cooking and lighting), or with potentially unsustainable alternatives (e.g., expanding grid-connected, coal-fired electricity supply), implying continued utility for socio-technical transitions perspectives within low-income contexts.…”
Section: National Contexts For Fostering Innovation Including Technomentioning
confidence: 99%
See 3 more Smart Citations